Affirmative action in higher education: redistribution, recognition, and representation in dispute (PerCursos, 2026)
This article analyzes the trajectory of affirmative action policies in Brazil, highlighting their historical and normative milestones, especially Law Nº 12.711/2012, known as the Quota Law, and its recent revisions. Drawing on the symbolic reference of Sankofa, which evokes the need to look to the past in order to build the present and the future, the paper revisits the role of the Black Movement, intellectuals, and diverse social actors in the struggle for the democratization of higher education and the consolidation of affirmative action as a state policy. Its main objective is to understand the advances, limits, and tensions of these policies in undergraduate and graduate education, while examining their emancipatory potential in the face of structural racism and persistent inequalities. Methodologically, the study combines Nancy Fraser’s three-dimensional theory of social justice — redistribution, recognition, and representation — with the cognitive approach to public policy (Muller and Surel) and critical discourse analysis (Faircloug and van Dijk). This theoretical-methodological framework makes it possible to examine both the normative design and the cognitive frames that structure the quota policies, as well as the hegemonic and counter-hegemonic discourses that dispute their legitimacy. The findings show that, although affirmative action policies have significantly expanded the access of Black, Indigenous, and low-income students to universities, challenges remain regarding student retention, the decolonization of curricula, the expansion of faculty diversity, and the strengthening of graduate education. The article concludes that such policies, far from being concessions, constitute a historical right and a horizon of social justice, essential to the democratization of universities and Brazilian society.
Keywords: affirmative action; higher education; social justice